Hemispheric Asymmetries of Magnetosphere-Ionosphere-Thermosphere Dynamics - Perlongo, Nicholas
The geospace environment, comprised of the magnetosphere-ionosphere-thermosphere system, is a highly variable and non-linearly coupled region. The dynamics of the system are driven primarily by electromagnetic and particle radiation emanating from the Sun that occasionally intensify into what are known as solar storms. Understanding the interaction of these storms with the near Earth space environment is essential for predicting and mitigating the risks associated with space weather that can irreparably damage spacecraft, harm astronauts, disrupt radio and GPS communications, and even cause widespread power outages. The geo-effectiveness of solar storms has hemispheric, seasonal, local time, universal time, and latitudinal dependencies. This dissertation investigates those dependencies through a series of four concentrated modeling efforts. The first study focuses on how variations in the solar wind electric field impact the thermosphere at different times of the day. Idealized simulations using the Global Ionosphere Thermosphere Model (GITM) revealed that perturbations in thermospheric temperature and density were greater when the universal time of storm onset was such that the geomagnetic pole was pointed more towards the sun. This universal time effect was greater in the southern hemisphere where the offset of the geomagnetic pole is larger. The second study presents a model validation effort using GITM and the Thermosphere Ionosphere Electrodynamics General Circulation Model (TIE-GCM) compared to GPS Total Electron Content (TEC) observations. The results were divided into seasonal, regional, and local time bins finding that the models performed best near the poles and on the dayside. Diffuse aurora created by electron loss in the inner magnetosphere is an important input to GITM that has primarily been modeled using empirical relationships. In the third study, this was addressed by developing the Hot Election Ion Drift Integrator (HEIDI) ring current model to include a self-consistent description of the ...